Statement by the Managing Director on the Independent Evaluation Office Report on the IMF Financial Surveillance. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2019)
The IEO report provides a welcome opportunity to reflect on the IMF's initiatives to expand and deepen its financial surveillance work in response to the Global Financial Crisis. In order to improve the relevance and traction of bilateral financial surveillance, the IMF needs to deepen financial and macrofinancial analysis, particularly in Article IV consultations, including by taking practical steps to better integrate Financial Sector Assessment Program analysis in Article IV consultations and by increasing financial skills and expertise among staff. The IMF should continue to work to enhance the impact of IMF multilateral surveillance by increasing rigor and transparency, and by deepening collaboration with international partners. On scaling-up the IMF's work with the international regulatory agencies to assess the impact of reforms, the IMF has undertaken several assessments of different aspects of the reforms following the 2012 Financial Surveillance Strategy. Some of these have been conducted jointly with the Standard Setting Bodies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Budget Discussion; Country Selection; FSAP Resource; PP; Refocusing FSAP Country Selection